Arquitectura paralela robótica: modelado y simulación con siemens nx® - Forero Casallas, John Alejandro; Ruiz Rosas, Víctor Elberto; Hurtado Cortés, Luini Leonardo (Visión electrónica, 2015)
This article describes the development of parallel architecture using Siemens NX ® platform modeling shown-, given as multifunctional devices designed to move parts or tools through programmed to perform specific tasks movements, consisting of kinematic chains connected to a fixed link. Through the kinematic trajectories versus time links joined by joints which limit their mobility are studied. The development perspective shown is on track to guide classroom implementations of basic robotics labs.